A Novel Strategy to Isolate Ubiquitin Conjugates Reveals Wide Role for Ubiquitination during Neural Development. - Franco, M.; Seyfried, N.T.; Brand, A.H.; Peng, J.; Mayor, U. (Molecular and Cellular Proteomics, 2011)
Ubiquitination has essential roles in neuronal development and function. Ubiquitin proteomics studies on yeast and HeLa cells have proven very informative, but there still is a gap regarding neuronal tissue-specific ubiquitination. In an organism context, direct evidence for the ubiquitination of neuronal proteins is even scarcer. Here, we report a novel proteomics strategy based on the in vivo biotinylation of ubiquitin to isolate ubiquitin conjugates from the neurons of Drosophila melanogaster embryos. We confidently identified 48 neuronal ubiquitin substrates, none of which was yet known to be ubiquitinated. Earlier proteomics and biochemical studies in non-neuronal cell types had identified orthologs to some of those but not to others. The identification here of novel ubiquitin substrates, those with no known ubiquitinated ortholog, suggests that proteomics studies must be performed on neuronal cells to identify ubiquitination pathways not shared by other cell types. Importantly, several of those newly found neuronal ubiquitin substrates are key players in synaptogenesis. Mass spectrometry results were validated by Western blotting to confirm that those proteins are indeed ubiquitinated in the Drosophila embryonic nervous system and to elucidate whether they are mono- or polyubiquitinated. In addition to the ubiquitin substrates, we also identified the ubiquitin carriers that are active during synaptogenesis. Identifying endogenously ubiquitinated proteins in specific cell types, at specific developmental stages, and within the context of a living organism will allow understanding how the tissue-specific function of those proteins is regulated by the ubiquitin system.